2005
DOI: 10.1073/pnas.0503392102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes required for cellulose synthesis by regression analysis of public microarray data sets

Abstract: Coexpression patterns of gene expression across many microarray data sets may reveal networks of genes involved in linked processes. To identify factors involved in cellulose biosynthesis, we used a regression method to analyze 408 publicly available Affymetrix Arabidopsis microarrays. Expression of genes previously implicated in cellulose synthesis, as well as several uncharacterized genes, was highly coregulated with expression of cellulose synthase (CESA) genes. Four candidate genes, which were coexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
586
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(624 citation statements)
references
References 43 publications
29
586
1
2
Order By: Relevance
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 86%
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to COBRA, five other members of this superfamily have been identified and characterized in plants. AtCOBL4 is required for cellulose biosynthesis in the secondary cell wall in Arabidopsis (Brown et al 2005;Persson et al 2005). AtCOBL9 is required for tip-directed growth in root hair development in Arabidopsis (Parker et al 2000;Jones et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Further, additional research tools of functional genomics in rice, such as full-length cDNA collection and whole genome expression profiling, have been established and have enhanced the pace for elucidating gene function throughout the genome . The combination of expression profiling and insertional mutagenesis strategies has been successful in assigning functions to several COBRA-like genes, such as AtCOBL4 and AtCOBL9 (Brown et al 2005;Persson et al 2005;Parker et al 2000;Jones et al 2006). As for COBRA-like genes in rice, only BC1 has been characterized and the functions of the other OsBC1Ls remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several new genes were found to be co-expressed with these CESAs and characterized as displaying cellulose synthesis deficiencies. 14,15 Further examples where these databases and/or methods have been used for candidate gene discovery encompass different processes such as starch metabolism, 16,17 seed germination 18 and shade avoidance. 19 However, many of these approaches rely primarily on simple Pearson correlation, sometimes coupled with network clustering approaches 20 or sequence analysis.…”
Section: Introductionmentioning
confidence: 99%